2018
DOI: 10.1016/j.tem.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Brain Feeding Circuits after Roux-en-Y Gastric Bypass

Abstract: Metabolic surgical procedures, such as Roux-en-Y gastric bypass (RYGB), uniquely reprogram feeding behavior and body weight in obese subjects. Clinical neuroimaging and animal studies are only now beginning to shed light on some of the underlying central mechanisms. We present here the roles of key brain neurotransmitter/neuromodulator systems in food choice, value, and intake at various stages after RYGB. In doing so, we elaborate on how known signals emanating from the reorganized gut, including peptide horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 125 publications
(220 reference statements)
0
19
0
1
Order By: Relevance
“…The central nervous system, especially the hypothalamus, can control the central and peripheral energy homeostasis through neuropeptides and neurotransmitters [59]. Some studies have confirmed that changes in the nervous system can be significantly observed after RYGB [60][61][62]. Liver fat metabolism is regulated by not only humoral but also the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…The central nervous system, especially the hypothalamus, can control the central and peripheral energy homeostasis through neuropeptides and neurotransmitters [59]. Some studies have confirmed that changes in the nervous system can be significantly observed after RYGB [60][61][62]. Liver fat metabolism is regulated by not only humoral but also the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…To conclude this section on interventional strategies, it is interesting to evoke what is still one of the most effective therapeutic compromises against morbid obesity: the Roux-en-Y gastric bypass (RYGB; Kang and Le, 2017). A recent paper reviewed the evidences derived from neuroimaging and animal (mainly rodent) studies (Hankir et al, 2018), explaining how a metabolic surgical procedure such as the RYGB, which is drastically reorganizing gut, including peptide hormones and microbiota metabolites, is also reshaping homeostatic and hedonic brain processes. Different animal models of bariatric surgery have been described (Rao et al, 2010), and the first demonstrations of RYGB in the pig model, to our knowledge, date back to the 1990s (Frantzides et al, 1995;Potvin et al, 1997).…”
Section: Impact Of Bariatric Surgery On Brain Activitymentioning
confidence: 99%
“…An early demonstration of neural regulation of insulin release was in rats fed sham meals, or entrained to stimuli related to eating. 9,[12][13][14] It is clear that GB has substantial effects on brain centres controlling feeding behaviour 15 ; thus, it is plausible that the CNS also affects islet hormone release after surgery. 10,12 Both cephalic 11 and prandial 10 insulin secretion is mediated in great part by parasympathetic stimuli carried in the vagus nerve.…”
Section: Introductionmentioning
confidence: 99%
“…10,12 Both cephalic 11 and prandial 10 insulin secretion is mediated in great part by parasympathetic stimuli carried in the vagus nerve. 9,[12][13][14] It is clear that GB has substantial effects on brain centres controlling feeding behaviour 15 ; thus, it is plausible that the CNS also affects islet hormone release after surgery.…”
mentioning
confidence: 99%